SEMIOLOG R. BARTHES AND SOCIAL MYTH: TODAY’S READING - Irina F. Ponizovkina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article deals with today’s reading of creative works by the prominent French semiologist R. Barthes. It reveals key aspects of the researcher’s contribution to the development of philosophy and methodology of studying modern myth. The author discusses powerful forces and substantional nature of language as a symbol system, which acts actively in social media as special connotative senses. They form a concealed language space of modern myth creation, which is not realized by society and individuals. By the early 21st century social myth creation had enlarged its functional field in the world and became an important ideological means of attaining political, national and other objectives in the social media. R. Barthes’s concept of mythology is gaining special topicality today, which complements an intricate and tricky model of modern social myth.